2018
DOI: 10.1038/s41467-018-06853-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mTORC1 by lncRNA H19 via disrupting 4E-BP1/Raptor interaction in pituitary tumours

Abstract: Aberrant expression of long noncoding RNA H19 has been associated with tumour progression, but the underlying molecular tumourigenesis mechanisms remain largely unknown. Here, we report that H19 expression is frequently downregulated in human primary pituitary adenomas and is negatively correlated with tumour progression. Consistently, upregulation of H19 expression inhibits pituitary tumour cell proliferation in vitro and tumour growth in vivo. Importantly, we uncover a function of H19, which controls cell/tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 68 publications
(84 reference statements)
1
85
0
Order By: Relevance
“…Many studies have shown that targeting some high-frequency hub-molecules in Table 1 has achieved good results in other types of pituitary adenomas. For example, TGFβ1 is used as a novel therapeutic target to treat resistant prolactinomas (66); the microRNA-145 inhibits the activation of the mTOR signaling by targeting AKT3 to suppress the proliferation and invasion of invasive pituitary adenoma cells (67); lncRNA H19 inhibits mTORC1 by disrupting 4E-BP1/Raptor interaction in pituitary tumors (68); and MAPK Pathways act as therapeutic targets in pituitary tumors (69). Because PI3K/Akt/mTOR and ERK/MAPK signaling pathways are significantly dysregulated in NFPA, and these two essential signaling pathways are not only related to rapid proliferation and apoptosis resistance of tumor cells, but also can regulate the activities of many other pathways and then regulate tumor growth in the multiple levels.…”
Section: Mapk Pathways Were Dysregulated In Nfpasmentioning
confidence: 99%
“…Many studies have shown that targeting some high-frequency hub-molecules in Table 1 has achieved good results in other types of pituitary adenomas. For example, TGFβ1 is used as a novel therapeutic target to treat resistant prolactinomas (66); the microRNA-145 inhibits the activation of the mTOR signaling by targeting AKT3 to suppress the proliferation and invasion of invasive pituitary adenoma cells (67); lncRNA H19 inhibits mTORC1 by disrupting 4E-BP1/Raptor interaction in pituitary tumors (68); and MAPK Pathways act as therapeutic targets in pituitary tumors (69). Because PI3K/Akt/mTOR and ERK/MAPK signaling pathways are significantly dysregulated in NFPA, and these two essential signaling pathways are not only related to rapid proliferation and apoptosis resistance of tumor cells, but also can regulate the activities of many other pathways and then regulate tumor growth in the multiple levels.…”
Section: Mapk Pathways Were Dysregulated In Nfpasmentioning
confidence: 99%
“…Studies have reported that the long non-coding RNA (lncRNA) RP11 promotes colorectal cancer cells dissemination by ZEB1 overexpression, whereas lncRNA HCCL5 could be activated by ZEB1 to promote hepatocellular carcinoma malignancy. 18,19 Among these, lncRNAs are a class of ncRNAs of more than 200 bp that have been demonstrated to be closely related to cancer progression, including tumorigenesis, 20 stemness, 21 apoptosis, 22 25 It has also been reported that LINC00511 promotes proliferation in pancreatic ductal adenocarcinoma, 26 ovarian cancer 27 and glioma. 16,17 Non-coding RNAs (ncRNAs) are transcribed genes that are not further translated into proteins and include lncRNAs, circular RNAs (circRNAs) and miRNAs, which perform vital roles in human cancers.…”
mentioning
confidence: 99%
“…This indicated lncRNA H19 is a potential target for the study of invasive GHPAs [18]. LncRNA H19 could also be acted as a tumor suppressor to inhibit the pituitary tumor growth [19]. LncRNA SNHG1 activated the TGFBR2/SMAD3 and RAB11A/Wnt/β-catenin pathways to promote the progression of pituitary tumors by sponging miR-302/372/373/520 in pituitary tumor cells [20].…”
Section: Of 17mentioning
confidence: 98%